DDX3X, the X homologue of AZFa gene DDX3Y, expresses a complex pattern of transcript variants only in the male germ line - Rauschendorf, Marc-Alexander; Zimmer, Jutta; Ohnmacht, Caroline; Vogt, Peter H. (Molecular human reproduction, 2014)
Abstract. DDX3X, the functional X homologue of the major AZFa gene, DDX3Y, belongs to the highly conserved PL10-subfamily of DEAD-box RNA helicase genes which
Gesehen am 29.07.2019